RSBP15 interacts with and stabilizes dRSPH3 during sperm axoneme assembly in Drosophila. (20th June 2019) - Wang, Ya; Xu, Rui; Cheng, Yiwei; Cao, Haowei; Wang, Zibin; Zhu, Tianyu; Jiang, Jiayin; Zhang, Hao; Wang, Chang; Qi, Lin; Liu, Mingxi; Guo, Xuejiang; et al.
Abstract: Flagellum in sperm is composed of over 200 different proteins and is essential for sperm motility. In particular, defects in the assembly of the radial spoke in the flagellum result in male infertility due to loss of sperm motility. However, mechanisms regulating radial spoke assembly remain unclear in metazoans. Here, we identified a novel Drosophila protein radial spoke binding protein 15 (RSBP15) which plays an important role in regulating radial spoke assembly. Loss of RSBP15 results in complete lack of mature sperms in seminal vesicles (SVs), asynchronous individualization complex (IC) and defective "9 + 2" structure in flagella. RSBP15 is colocalized with dRSPH3 in sperm flagella, and interacts with dRSPH3 through its DD_R_PKA superfamily domain which is important for the stabilization of dRSPH3. Moreover, loss of dRSPH3, as well as dRSPH1, dRSPH4a and dRSPH9, showed similar phenotypes to rsbp15 KO mutant. Together, our results suggest that RSBP15 acts in stabilizing the radial spoke protein complex to anchor and strengthen the radial spoke structures in sperm flagella.